DLL3 expression in large cell neuroendocrine carcinoma (LCNEC) and association with molecular subtypes and neuroendocrine profile. (December 2019) - Hermans, B.C.M.; Derks, J.L.; Thunnissen, E.; van Suylen, R.J.; den Bakker, M.A.; Groen, H.J.M.; Smit, E.F.; Damhuis, R.A.; van den Broek, E.C.; Ruland, A.; Speel, E.J.M.; Dingemans, A.M.C.; et al.
Highlights: DLL3 is expressed in 74% of stage IV LCNEC patients The majority (80%) has cytoplasmic/membranous expression DLL3 is expressed in both SCLC- and NSCLC-like LCNEC subtype 6/6 STK11mt, 10/11 KEAP1mt and 9/9 TP53wt tumors were DLL3 positive DLL3 expression is associated with expression of ASCL1 and neuroendocrine markers Abstract: Objectives: For stage IV pulmonary large cell neuroendocrine carcinoma (LCNEC), the only therapeutic option is palliative chemotherapy. DLL3 is a new therapeutic target, which seems to be often expressed in SCLC and LCNEC. It has recently been reported that DLL3 mRNA expression is particularly upregulated in the LCNEC subgroup with STK11/KEAP1 and TP53 co-mutations, in contrast to lower expression levels in RB1 and TP53 co-mutated LCNEC. Our aim was to investigate DLL3 protein expression in stage IV LCNEC and correlate data with mutational profiles ( i.e.STK11/KEAP1/RB1 ), immunostaining results (pRb, NE markers) and clinical characteristics. Materials and Methods: Immunohistochemical analysis for DLL3 (SC16.65) and ASCL1 (SC72.201) was performed on 94 and 51 FFPE tissue sections, respectively, of pathologically reviewed stage IV LCNEC. DLL3 and ASCL1 were scored positive if ≥1% of the tumor cells showed cytoplasmic/membranous or dotlike (DLL3) or nuclear (ASCL1) immunostaining. Data were correlated with available sequencing ( TP53, RB1, STK11, KEAP1), immunostaining (pRb, NE markers) and clinical data. Results: DLL3 was expressed in 70/94 (74%) LCNEC, 56 (80%) of which showed cytoplasmic/membranous staining. Median H-score was 55 (interquartile range 0–160). DLL3 staining was not different in pRb immunohistochemistry negative and positive patients (DLL3+ in 53/70 (76%) vs . 14/21 (67%), p = 0.409) or RB1 mutated and wildtype patients (DLL3+ in 27/34 (79%) vs . 23/33 (70%), p = 0.361). Nevertheless, 6/6 (100%) STK11 mutated, 10/11 (91%) KEAP1 mutated and 9/9 (100%) TP53 wildtype tumors were DLL3+ . Furthermore, DLL3 expression was associated with expression of ASCL1 and at least 2 out of 3 neuroendocrine markers. Conclusion: The high percentage (74%) of DLL3 expression in stage IV LCNEC denotes the potential of DLL3 targeted therapy in this patient group.